LOYALITAS WISATAWAN TERHADAP KOTA BANDA ACEH SEBAGAI DESTINASI WISATA HALAL INDONESIA DENGAN KEPUASAN WISATAN SEBAGAI MEDIASI - Joni Setiawan, Muhammad Ridha Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
This study aims to determine the effect of destination image on tourists loyalty with variables tourists satisfaction as mediators. The sample used in this study is 114 respondents who are visit halal tourism in Banda Aceh. Purposive Sampling is used as a sampling technique. Partial Least Square analysis method is used as an analytical method to determine the effect of the variables involved. The results of this study indicate that destination image has effect on tourists loyalty. In addition, the results obtained that the tourists satisfaction variables partially influence the destination image to tourists loyalty. The higher destination image, the higher the tourists satisfaction, the stronger the tourists loyalty of the tourists. Keyword : Destination Image, Tourist Satisfaction, Tourists Loyalty, Halal Tourism